2022
DOI: 10.1098/rspb.2022.1011
|View full text |Cite
|
Sign up to set email alerts
|

Home and hub: pet trade and traditional medicine impact reptile populations in source locations and destinations

Abstract: The pet trade and Traditional Chinese Medicine (TCM) consumption are major drivers of global biodiversity loss. Tokay geckos ( Gekko gecko ) are among the most traded reptile species worldwide. In Hong Kong, pet and TCM markets sell tokay geckos while wild populations also persist. To clarify connections between trade sources and destinations, we compared genetics and stable isotopes of wild tokays in local and non-local populations to dried individuals from TCM markets across Hong Kong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Moreover, trade records from other regions are also on the magnitude of millions of individuals per year (Caillabet, 2013). However, it should be noted that our estimation does not include the pet trade and other potential trade types, which are of significant size according to other studies (Dufour et al, 2022). Therefore, HK's actual gecko trade volume could be higher than our estimation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, trade records from other regions are also on the magnitude of millions of individuals per year (Caillabet, 2013). However, it should be noted that our estimation does not include the pet trade and other potential trade types, which are of significant size according to other studies (Dufour et al, 2022). Therefore, HK's actual gecko trade volume could be higher than our estimation.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, HK's actual gecko trade volume could be higher than our estimation. On the other hand, the CITES records for HK only report imports from Indonesia and Thailand, yet genetic data from Dufour et al (2022) reveal other potential origins of geckos traded in HK, including mainland China. The absence of mainland China in the CITES trade records suggests these products are likely to be illegal.…”
Section: Trade Legality and Quantitymentioning
confidence: 99%
See 1 more Smart Citation
“…comm.) and Hong Kong (Dufour et al 2022), due both to deliberate introductions (e.g., King andKrakauer 1966, Breuil 2009) and accidental escapes (e.g., Behm et al 2019). As a result of multiple intentional releases in Florida from the 1960s onwards (King andKrakauer 1966, Krysko et al 2019), tokay geckos have established throughout much of the state (Krysko et al 2019), and have been reported from as far south as Key West (Meshaka et al 2004) and as far north as Leon County (Means 1996), which borders Georgia.…”
Section: Introductionmentioning
confidence: 99%
“…Hong Kong is a special administrative region of China with a dense human population, in which members of the public can purchase exotic reptiles, including turtles, to keep as pets. Exotic reptiles are traded at markets such as the popular Tung Choi Street in Mong Kok, Hong Kong's largest pet market (Sung et al 2021a;Dufour et al 2022), as well as through online selling (Sung and Fong 2018). The release of exotic pets has been linked to the establishment of introduced species of reptiles that include the Red-eared Slider (Trachemys scripta elegans) Sung et al 2021b), the Chinese Striped-necked Turtle (Mauremys sinensis) (Sung et al 2021b), Tokay Gecko (Gekko gecko) (Romer 1951), Brook's House Gecko (Hemidactylus brookii) (Romer 1977), and Chinese Water Dragon (Physignathus cocincinus) (Mo 2019a).…”
mentioning
confidence: 99%